2019
DOI: 10.1093/cid/ciz1213
|View full text |Cite
|
Sign up to set email alerts
|

Darunavir/Cobicistat/Emtricitabine/Tenofovir Alafenamide in a Rapid-Initiation Model of Care for Human Immunodeficiency Virus Type 1 Infection: Primary Analysis of the DIAMOND Study

Abstract: Background Most guidelines recommend rapid treatment initiation for patients with newly diagnosed human immunodeficiency virus type 1 (HIV-1) infection, but prospective US data are limited. The DIAMOND (NCT03227861) study using darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg is a phase 3 prospective study evaluating efficacy/safety of a single-tablet regimen in a rapid-initiation model of care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
2
28
1
1
Order By: Relevance
“…These clinical trials were conducted over more than a 10-year span, providing 5291 patientyears of experience with this regimen. 20,21,23,30 A limitation of the analysis is that the studies did not include integrase inhibitor-based regimens, which were not available at the time that some of the studies in this analysis took place. Additionally, the analysis reported here only includes data from controlled clinical trials and does not include real-world data.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These clinical trials were conducted over more than a 10-year span, providing 5291 patientyears of experience with this regimen. 20,21,23,30 A limitation of the analysis is that the studies did not include integrase inhibitor-based regimens, which were not available at the time that some of the studies in this analysis took place. Additionally, the analysis reported here only includes data from controlled clinical trials and does not include real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…Methodological details for the seven clinical studies included in the previous analysis have been described. 6,[10][11][12][13][14][15][16] Detailed methods for the three recent studies of the D/C/F/TAF STR have also been reported [19][20][21][22][23] and are briefly summarized here. Key study design information for all 10 studies is shown in Supplemental Figure S1.…”
Section: Study Designsmentioning
confidence: 99%
See 3 more Smart Citations